ANALISI PENGEMBANGAN BISNIS TACOCOK (Studi Kasus Pada Produk Tacocok) - Muhammad Rifqi Althaf Dwiputra; Shoimatul Fitria (Faculty of Economics and Business Diponegoro University, 2022)
The development of a food & beverage business can be done by analyzing various aspects to measure the opportunities of the business such as production aspects, market and marketing aspects, human resources aspects, operational aspects, financial aspects, legal aspects, social aspects, environmental aspects, and economic aspects. This research uses descriptive qualitative method where data is collected through observation, questionnaires, and literature study. The results of this study indicate that food & beverages businesses that offer Mexican food products have good opportunities in the city of Bogor. The business development of the food & beverage business requires funding of Rp. 91,728,534 which consists of an investment cost of Rp. 7,055,500. Funds issued can generate a Net Present Value of Rp 173,630,413, Internal Rate of Return (IRR) of 39%, Benefit Cost Ratio of 1.24 and a rate of return or Payback Period for 3 years 9 months. From the calculation of the sensitivity analysis, it can be said that the business development of food & beverages can be implemented and is feasible or feasible to run.